Rate-Splitting Multiple Access With Finite-Alphabet Constellations: Precoder Optimization and Achievable Rate Performance - Mi, De; Chen, Hongzhi; Chu, Zheng; Xiao, Pei; Wu, Yiyan; Wang, Chin-Liang (IEEE transactions on green communications and networking, 2024)
Rate Splitting Multiple Access (RSMA) precoder design with the practical finite-alphabet constellations instead of Gaussian inputs has been addressed in this paper. Considering a multiuser (MU) multiple-input single-output (MISO) broadcast channel (BC) system, we derive a generalized expression of the achievable rate for each user, in a way that the derived expression is generically applicable, e.g., for both underloaded and overloaded cases. Building upon the achievable rate expression, we formulate a multi-objective problem that maximizes the weighted sum rate (WSR) of the considered system, which incorporates with the optimization of the RS precoder for both common and private symbol streams in RSMA. The emphasis here is that our derivation of the achievable rate expression, the problem formulation of the WSR and the optimization of the RSMA precoder all involve the finite alphabet constellation constraint. An iterative gradient descent algorithm with alternative optimization and line search methods is applied to solve the optimization problem. Numerical results show that RSMA can reach the maximum achievable WSR, under both underloaded and overloaded scenarios, with less transmit power compared to the traditional schemes, e.g., space division multiple access (SDMA) and power-domain non-orthogonal multiple access (NOMA). Moreover, thanks to its flexibility, RSMA subsumes both SDMA and NOMA as its subset to fit into different scenarios such as underloaded and overloaded cases with different constellation sizes.